Early Physical Therapy Management of a Patient with Diaphragmatic Eventration Following Diaphragmatic Plication: A Case Report - Prajapati, Dipika; Ashok, Abeeshna (Journal of Health and Allied Sciences NU, 2024)
Diaphragmatic plication is the recommended surgical procedure for the treatment of diaphragmatic eventration in those who have failed conservative care. The present case report describes a 63-year-old male patient who presented with breathlessness on exertional activities. Chest X-ray and Computed Tomography (CT) of the thorax revealed diaphragmatic eventration on the right side. After failed conservative management, the patient underwent diaphragmatic plication surgery and was followed up with postoperative physical therapy management. Physical therapy intervention was started from 3 days postsurgery and was continued for 1 week. The treatment goals focused on reducing breathlessness, reducing pain on the incision site, preventing postoperative complications, and improving functional capacity. The present study highlights the benefits of early physical therapy interventions including incentive spirometer, dyspnea relieving techniques, Transcutaneous Electrical Nerve Stimulation (TENS), and light- to moderate-intensity aerobic exercises in the patient after plication surgery.
Keywords: diaphragmatic eventration; diaphragmatic plication; physical therapy; rehabilitation